Folk Schools as Inspiration for Contemporary Democratic Peacebuilding. Issue 3 (December 2018) - Klein, Mike
Cultivation of democratic culture is a potential antidote to radical disagreement, contradiction, and polarisation. Folk high schools (folkehøjskoles) emerged in Denmark following a nonviolent revolution from monarchy to democracy in 1849 and were founded as non-formal educational institutions for the cultivation of a pervasive democratic culture. The Scandinavian folk school tradition emerged in the US to meet diverse democratic needs for: adult education, community building, labour organising, and social movement leadership. The Highlander Folk School embodied the democratising leadership of the early Danish folk schools as it shaped the US labour, civil rights, and environmental movements. Folk schools as popular non-formal education hold promise for developing a culture of democratic preventative peacebuilding to foster individual and collective agency; advance a vital agonistic democracy; and counter the politics of fear, division, and polarisation.